2010
DOI: 10.1212/wnl.0b013e3181ed9e7c
|View full text |Cite
|
Sign up to set email alerts
|

Lithium carbonate in amyotrophic lateral sclerosis

Abstract: The study provides Class II evidence that therapeutic (0.4-0.8 mEq/L) vs subtherapeutic (0.2-0.4 mEq/L) lithium carbonate did not differ in the primary outcome of efficacy (survival/loss of autonomy) in ALS. Both target levels led to dropouts in more than 30% of participants due to patient-perceived lack of efficacy and AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 23 publications
5
55
0
1
Order By: Relevance
“…19,44 Recently, a Class II clinical trial provided evidence that therapeutic or subtherapeutic doses of lithium lack efficacy in clinical improvement for ALS patients. 20 Furthermore, concerns about the safety of lithium carbonate as a treatment for ALS patients have been raised after the halting of a trial that saw serious adverse effects in its participants.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…19,44 Recently, a Class II clinical trial provided evidence that therapeutic or subtherapeutic doses of lithium lack efficacy in clinical improvement for ALS patients. 20 Furthermore, concerns about the safety of lithium carbonate as a treatment for ALS patients have been raised after the halting of a trial that saw serious adverse effects in its participants.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…[18][19][20] Since lithium is a multifunctional drug, it is very difficult to verify whether the therapeutic effects of lithium in ALS mice are directly related to autophagy. Thus, it is important to test more selective autophagy modulators in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 One enrolled 84 patients taking riluzole and was powered to detect the large positive effect reported in the initial trial. 2 It was stopped at the first interim analysis for futility against this endpoint.…”
Section: Figure 2 Als Functional Rating Scale-revised (Alsfrs-r) Slopmentioning
confidence: 99%
“…The other enrolled 171 patients who were randomly assigned to either a subtherapeutic or a higher therapeutic dose of lithium. 12 That study was stopped prematurely because of excessive dropouts and found no differences in efficacy measures between the groups or compared with control subjects from a disease registry. 12 Our findings provide additional information about longer treatment duration, safety concerns, and a trial design with historical controls.…”
Section: Figure 2 Als Functional Rating Scale-revised (Alsfrs-r) Slopmentioning
confidence: 99%
See 1 more Smart Citation